Material Deprivation as Phenomenon of Poverty: Revitalisation Foreshortening - Hoshovska, Daria; Hoshovskyj, Yaroslav (Psychological Prospects Journal, 2016)
In the article the base going is reflected near understanding of semantic and functional essence of the phenomenon of material deprivation. The negative and brake role of deprived limits is marked on common personality development of man. A key concept of economic deprivation “poverty” is examined not only as a social action, but as the special isolation, predetermined by absence of economic resources. It is marked that economic deprivation brings in substantial disorder in vital activity of a financially dependent person, adds aggressiveness, anxiety and conflict to his/her behaviour. It is established that the symptoms of economic deprivation is a non-constructive conduct, which reduces stimulant and motivational potentials of man, results in desadaptation, stresses and frustration. It is marked that general nevrotisation of a financially dependent person shows up the outlook in negative the emotional states, mode of oppression of psyche, and and social activity. It is marked that deprivation threatens the depth and power of economic to valuable development on all levels, results in original involution − social outsider. It is marked that social frustration of deprived personality which is expressed in dissatisfaction by own public achievements in the basic aspects of vital functions, in particular at the level of inadequate material status, can result in deep violations in Self-concept and consciousness. It is set that the problems of neutralization of destructive consequences of economic deprivation on the psyche of personality except for bringing in of social and psychological rehabilitation Technologies need decision also on macroeconomic level. Basic directions of revitalisation of financially dependent people are reflected due to bringing in modern рsychological rehabilitation technologies.Keywords: poverty, deprivation, material deprivation, economic deprivation, opposition “poor – rich”, revitalisation.